2022
DOI: 10.3390/ani12192487
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinolysis in Dogs with Intracavitary Effusion: A Review

Abstract: Physiologic fibrinolysis is a localized process in which stable fibrin strands are broken down by plasmin in response to thrombosis. Plasmin activation can also take place separately from the coagulation process, resulting in pathologic fibrinolysis. When plasmin activation exceeds the neutralizing capacity of plasmin inhibitors, severe bleeding can potentially take place. Although the processes which regulate coagulation and fibrinolysis in the blood are well known, it is less clear as to what extent the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…uPA has been associated with cancer cell migration, invasion, and modulation of cell adhesion, thereby promoting the formation and progression of various cancers ( 19 , 20 ). uPA is also known to catalyze the conversion of plasminogen into plasmin without negative feedback, resulting in the breakdown of fibrin clots and the degradation of the extracellular matrix ( 18 , 21 , 22 ). This pathogenesis results in the development of secondary hyperfibrinolysis as the resultant hypofibrinogenemia is the result of imbalanced excessive activation of structurally normal fibrinolytic enzymes or enhanced susceptibility of fibrin to proteolysis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uPA has been associated with cancer cell migration, invasion, and modulation of cell adhesion, thereby promoting the formation and progression of various cancers ( 19 , 20 ). uPA is also known to catalyze the conversion of plasminogen into plasmin without negative feedback, resulting in the breakdown of fibrin clots and the degradation of the extracellular matrix ( 18 , 21 , 22 ). This pathogenesis results in the development of secondary hyperfibrinolysis as the resultant hypofibrinogenemia is the result of imbalanced excessive activation of structurally normal fibrinolytic enzymes or enhanced susceptibility of fibrin to proteolysis ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reduction in factor VIII specifically has been associated with upregulation of the fibrinolytic system, resulting in secondary hyperfibrinolysis ( 23 ). Thus, when taken in tandem with the dog’s history of confirmed metastatic adenocarcinoma, thrombocytopenia, regenerative anemia, hypocoagulable profile on TEG ( Figure 1 ), and decreased platelet aggregation on impedance aggregometry ( Figure 2 ), the most likely cause for the dog’s progressive clinical decline is chronic DIC with a concurrent paraneoplastic secondary hyperfibrinolysis, a rare diagnosis in veterinary medicine ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…When this uncontrolled plasmin activity overwhelms the neutralizing effects of its inhibitors, it can lead to severe bleeding complications. In a 2022 study, Zoia et al demonstrated that coagulation followed by fibrinogenolytic activity occurs in dogs in all types of ascitic and pleural fluids, and that this increased fibrinolytic activity is also present in their blood, in some cases reaching a hyperfibrinolytic state [57]. While there is limited evidence of fibrinolysis in hematological malignancies [58,59], hyperfibrinogenolysis has also been detected in dogs with angiostrongylosis, neoplasia, liver disease, traumatic hemorrhagic shock, and other diseases [45,57].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2022 study, Zoia et al demonstrated that coagulation followed by fibrinogenolytic activity occurs in dogs in all types of ascitic and pleural fluids, and that this increased fibrinolytic activity is also present in their blood, in some cases reaching a hyperfibrinolytic state [57]. While there is limited evidence of fibrinolysis in hematological malignancies [58,59], hyperfibrinogenolysis has also been detected in dogs with angiostrongylosis, neoplasia, liver disease, traumatic hemorrhagic shock, and other diseases [45,57]. Based on the findings of the present study, a scenario of primary lymphoma-associated hyperfibrinolysis can be hypothesized.…”
Section: Discussionmentioning
confidence: 99%